PERAN DAN FUNGSI MASYARAKAT DALAM PEMBANGUNAN DESA - Ainol; Fathullah (Lembaga Penerbitan, Penelitian, dan Pengabdian Masyarakat (LP3M) UNZAHLP3M, 2021)
The community is one of the systems of a village that is obliged to be involved in village development activities. The community is involved from planning, programming to implementation, to monitoring sessions. Without the role of a citizen, it is impossible to make the villagers prosperous. The purpose of this research is to determine the role of residents in the development and construction of roads in the village of Karanggeger Pajarakan Probolinggo.(Minahasa, 2017) In this case, the theory used is Mikkelsen (1999: 64) in Isbandi's book (2007: 27), namely Participatory Planning Based on Community Assets. Research Methods: This type of research uses a qualitative descriptive approach. Sugiono (2002: 6) qualitative descriptive research is an activity carried out on independent variables, namely without making comparisons or connecting with other variables. The focus of the research is community participation in infrastructure development in the village of Karanggeger Pajarakan Probolinggo. Data processing is done by presenting data, reduction and drawing conclusions. The results of the study were reviewed from 5 indicators including; 1. community participation in contributing in this case community participation is low especially with very minimal meetings, 2. community participation in the sensitization process (sensitizing) in this case the government is not doing enough socialization so that the community is less sensitive to development, 3. Community participation with very high voluntary involvement in both labor and money, 4. community participation with an active process in this case the community is less active in participation and development and seems to be waiting for command, 5. community participation by conducting dialogue between the local community and staff in terms of this lack of dialogue between the community and the government.